2013
DOI: 10.3390/ijms14048393
|View full text |Cite
|
Sign up to set email alerts
|

A Convolutional Code-Based Sequence Analysis Model and Its Application

Abstract: A new approach for encoding DNA sequences as input for DNA sequence analysis is proposed using the error correction coding theory of communication engineering. The encoder was designed as a convolutional code model whose generator matrix is designed based on the degeneracy of codons, with a codon treated in the model as an informational unit. The utility of the proposed model was demonstrated through the analysis of twelve prokaryote and nine eukaryote DNA sequences having different GC contents. Distinct diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 31 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…The amino acid correspondence table is depicted below. and error-correcting information of adjacent codons [19]. In particular, it has been shown that there is a "strong short-range correlation of adjacent bases" and that adjacent genes are more likely to be co-expressed than non-adjacent genes [20] [11].…”
Section: Binary Representation Of Dna Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid correspondence table is depicted below. and error-correcting information of adjacent codons [19]. In particular, it has been shown that there is a "strong short-range correlation of adjacent bases" and that adjacent genes are more likely to be co-expressed than non-adjacent genes [20] [11].…”
Section: Binary Representation Of Dna Codesmentioning
confidence: 99%
“…Additionally, the expression patterns of adjacent genes are more correlated than patterns of randomly selected gene pairs [16]. In all, various studies have demonstrated that the nearby informational units have an effect on the current informational unit [19].…”
Section: Binary Representation Of Dna Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in mapping using the binary codes, Hamming distance and Euclidean distance were employed to reflect the differences between transition and transversion in light and dark colors, respectively, as shown in Fig. 3 [2,34,35] .…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…A convolutional encoding method was adopted, where the error-correction coding theory was used to encode and analyze DNA sequences for prokaryotic organisms [35] . The convolutional code model was designed based on degeneracy of codons.…”
Section: Error-correction Codementioning
confidence: 99%